Answer:
The measure of angle x is 40°
Step-by-step explanation:
we know that
The measurement of the outer angle is the semi-difference of the arcs which comprises
see the attached figure with letters to better understand the problem
so
m∠x=(1/2)[arc AB-arc AC]
<u><em>Find the measure of arc AC</em></u>
we know that
arc AB+arc BC+arc AC=360° ----> by complete circle
substitute the given values
arc AB=200°
arc BC=40°
arc AC=?
200°+40°+arc AC=360°
240°+arc AC=360°
arc AC=360°-240°=120°
<u><em>Find the measure of angle x</em></u>
m∠x=(1/2)[200°-120°]=40°
Answer:
1) ![\sqrt{1225}+\sqrt{1024}=67](https://tex.z-dn.net/?f=%5Csqrt%7B1225%7D%2B%5Csqrt%7B1024%7D%3D67)
2) ![\sqrt[3]{-1331}=-11](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B-1331%7D%3D-11)
3) Evaluating
we get ![p=\pm 4](https://tex.z-dn.net/?f=p%3D%5Cpm%204)
4) ![x^3+y^2+z \ when \ x=3, y=-2, x=-6 \ we \ get \ \mathbf{25}](https://tex.z-dn.net/?f=x%5E3%2By%5E2%2Bz%20%5C%20when%20%5C%20x%3D3%2C%20y%3D-2%2C%20x%3D-6%20%5C%20we%20%5C%20get%20%5C%20%5Cmathbf%7B25%7D)
5) ![\frac{(-6)^4\times(-2)^3\times(3)^3}{(-6)^6}=-6](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6%29%5E4%5Ctimes%28-2%29%5E3%5Ctimes%283%29%5E3%7D%7B%28-6%29%5E6%7D%3D-6)
Step-by-step explanation:
1) ![\sqrt{1225}+\sqrt{1024}](https://tex.z-dn.net/?f=%5Csqrt%7B1225%7D%2B%5Csqrt%7B1024%7D)
Prime factors of 1225 : 5x5x7x7
Prime factors of 1024: 2x2x2x2x2x2x2x2x2x2
![\sqrt{1225}+\sqrt{1024}\\=\sqrt{5\times5\times7\times7}+\sqrt{2\times2\times2\times2\times2\times2\times2\times2\times2\times2}\\=\sqrt{5^2\times7^2}+\sqrt{2^2\times2^2\times2^2\times2^2\times2^2}\\=5\times7+(2\times2\times2\times2\times2)\\=35+32\\=67](https://tex.z-dn.net/?f=%5Csqrt%7B1225%7D%2B%5Csqrt%7B1024%7D%5C%5C%3D%5Csqrt%7B5%5Ctimes5%5Ctimes7%5Ctimes7%7D%2B%5Csqrt%7B2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%7D%5C%5C%3D%5Csqrt%7B5%5E2%5Ctimes7%5E2%7D%2B%5Csqrt%7B2%5E2%5Ctimes2%5E2%5Ctimes2%5E2%5Ctimes2%5E2%5Ctimes2%5E2%7D%5C%5C%3D5%5Ctimes7%2B%282%5Ctimes2%5Ctimes2%5Ctimes2%5Ctimes2%29%5C%5C%3D35%2B32%5C%5C%3D67)
![\sqrt{1225}+\sqrt{1024}=67](https://tex.z-dn.net/?f=%5Csqrt%7B1225%7D%2B%5Csqrt%7B1024%7D%3D67)
2) ![\sqrt[3]{-1331}](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B-1331%7D)
We know that ![\sqrt[n]{-x}=-\sqrt[n]{x} \ ( \ if \ n \ is \ odd)](https://tex.z-dn.net/?f=%5Csqrt%5Bn%5D%7B-x%7D%3D-%5Csqrt%5Bn%5D%7Bx%7D%20%5C%20%28%20%5C%20if%20%5C%20n%20%5C%20is%20%5C%20odd%29)
Applying radical rule:
![\sqrt[3]{-1331}\\=-\sqrt[3]{1331} \\=-\sqrt[3]{11\times\11\times11}\\=-\sqrt[3]{11^3} \\Using \ \sqrt[n]{x^n}=x \\=-11](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B-1331%7D%5C%5C%3D-%5Csqrt%5B3%5D%7B1331%7D%20%5C%5C%3D-%5Csqrt%5B3%5D%7B11%5Ctimes%5C11%5Ctimes11%7D%5C%5C%3D-%5Csqrt%5B3%5D%7B11%5E3%7D%20%5C%5CUsing%20%5C%20%5Csqrt%5Bn%5D%7Bx%5En%7D%3Dx%20%5C%5C%3D-11)
So, ![\sqrt[3]{-1331}=-11](https://tex.z-dn.net/?f=%5Csqrt%5B3%5D%7B-1331%7D%3D-11)
3) ![2:p :: p:8](https://tex.z-dn.net/?f=2%3Ap%20%3A%3A%20p%3A8)
It can be written as:
![p*p=2*8\\p^2=16\\Taking \ square \ root \ on \ both \ sides\\\sqrt{p^2}=\sqrt{16}\\p=\pm 4](https://tex.z-dn.net/?f=p%2Ap%3D2%2A8%5C%5Cp%5E2%3D16%5C%5CTaking%20%5C%20square%20%5C%20root%20%5C%20on%20%5C%20both%20%5C%20sides%5C%5C%5Csqrt%7Bp%5E2%7D%3D%5Csqrt%7B16%7D%5C%5Cp%3D%5Cpm%204)
Evaluating
we get ![p=\pm 4](https://tex.z-dn.net/?f=p%3D%5Cpm%204)
4) ![x^3+y^2+z \ when \ x=3, y=-2, x=-6](https://tex.z-dn.net/?f=x%5E3%2By%5E2%2Bz%20%5C%20when%20%5C%20x%3D3%2C%20y%3D-2%2C%20x%3D-6)
Put value of x, y and z in equation and solve:
![x^3+y^2+z \\=(3)^3+(-2)^2+(-6)\\=27+4-6\\=25](https://tex.z-dn.net/?f=x%5E3%2By%5E2%2Bz%20%5C%5C%3D%283%29%5E3%2B%28-2%29%5E2%2B%28-6%29%5C%5C%3D27%2B4-6%5C%5C%3D25)
So, ![x^3+y^2+z \ when \ x=3, y=-2, x=-6 \ we \ get \ \mathbf{25}](https://tex.z-dn.net/?f=x%5E3%2By%5E2%2Bz%20%5C%20when%20%5C%20x%3D3%2C%20y%3D-2%2C%20x%3D-6%20%5C%20we%20%5C%20get%20%5C%20%5Cmathbf%7B25%7D)
5) ![\frac{(-6)^4\times(-2)^3\times(3)^3}{(-6)^6}](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6%29%5E4%5Ctimes%28-2%29%5E3%5Ctimes%283%29%5E3%7D%7B%28-6%29%5E6%7D)
We know (-a)^n = (a)^n when n is even and (-a)^n = (-a)^n when n is odd
![\frac{(-6)^4\times(-2)^3\times(3)^3}{(-6)^6}\\\\=\frac{1296\times-8\times 27}{46656}\\\\=\frac{-279936}{46656} \\\\=-6](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6%29%5E4%5Ctimes%28-2%29%5E3%5Ctimes%283%29%5E3%7D%7B%28-6%29%5E6%7D%5C%5C%5C%5C%3D%5Cfrac%7B1296%5Ctimes-8%5Ctimes%2027%7D%7B46656%7D%5C%5C%5C%5C%3D%5Cfrac%7B-279936%7D%7B46656%7D%20%5C%5C%5C%5C%3D-6)
So, ![\frac{(-6)^4\times(-2)^3\times(3)^3}{(-6)^6}=-6](https://tex.z-dn.net/?f=%5Cfrac%7B%28-6%29%5E4%5Ctimes%28-2%29%5E3%5Ctimes%283%29%5E3%7D%7B%28-6%29%5E6%7D%3D-6)
Can you repost this with a picture please ?
Since area is length times width, it would be the factors of the equation for the area.
X2+11x+28 factors into...
Length is x+7 so...
Width is x+4
Answer:
-21
Step-by-step explanation:
It would have to be -21 because there's -7, but the threes not negative so it would have to be -21